The Influence of Soft Skills & Hard Skills of Students in Facing Work Readiness with Self-Efficacy as an Intervening Variable - Sinaga, Juhari Volmer; Rosita, Sry; Chairunnisa, Fitri (Management Research and Behavior Journal, 2024)
This study aims to determine the effect of students' soft skills & hard skills in facing work readiness with self-efficacy as an intervening variable in students of the 2019 batch of Management Study Program students at the Faculty of Economics and Business at Jambi University. This type of research is quantitative research. The population in this study were all 183 students of the Bachelor of Management Study Program class of 2019 with a sample of 65 people. Data was collected using a questionnaire. The research data analysis method is descriptive statistical analysis using the Structural Equation Model (SEM) technique, with Partial Least Square (PLS) as a processing tool using the SmartPLS program. The results of this study indicate that soft skills havent a positive andnot significant effect on work readiness, hard skills havent a positive and not significant effect on work readiness, self-efficacy has a positive and significant effect on work readiness, soft skills have a positive and significant effect on self-efficacy, hard skills have an effect positive and significant on self-efficacy, then soft skills have a positive and significant effect on work readiness through self-efficacy, and hard skills have a positive and significant effect on work readiness through self-efficacy.